Observações da Espessura Óptica dos Aerossóis nos Açores - Carvalho, Fernanda; Henriques, Diamantino; Fialho, Paulo; Bettencourt, Vera (2005)
Comunicação apresentada no 4º Simpósio de Meteorologia e Geofísica da APMG – 6º Encontro Luso-Espanhol de Meteorologia, Sesimbra, 14-17 Fevereiro de 2005. First results of aerosol optical depth measurements out with a Middleton SP02 sun photometer mounted on a sun tracker system (Kipp & Zonen 2AP) in Terceira Is. (Azores) are presented. SP01 and Cimel data from AERONET programme at Faial Is. are compared and analyzed with respect to weather conditions. These measurements are a part of the Portuguese Meteorological contribution for the development of a Global Station in the scope of the GAW/WMO programme in close cooperation with Azores University. The installation and operation of these instruments are partially funded by CLIMAAT (INTERREG IIIB – Project CLIMAAT – MAC 2.3/A3). Ground based measurements collected at Terceira Is. should be useful on long term referencing and assessing of the performance of space-borne instruments over North Atlantic Region.